Principios basicos de la asociacion de cultivos - García, S.; Davis, J.H.C. (International Center for Tropical Agriculture, 1983)
The importance of traditional intercropping in the tropics is analyzed, mentioning statistics that emphasize the worldwide importance of this cropping system. Terms that describe multiple cropping systems are defined: sequential cropping (double, triple, and quadruple cropping, and ratooning), associated cropping (mixed, intercropping, strip, and relay cropping), sole cropping (monoculture), rotation, cropping pattern, and cropping system. Examples are given of associations with beans in Latin America and basic physiological, agronomic, genetic, pathological, entomological, economic, nutritive, and cultural factors are briefly analyzed. It is concluded that it is necessary to collect all the available information before establishing priorities; the research program should keep a permanent and close communication with the farmers to ensure a practical focusing of research and to assess the new technology to determine its effectiveness. (CIAT)